2022
DOI: 10.1097/ee9.0000000000000225
|View full text |Cite
|
Sign up to set email alerts
|

Joint association between ambient air pollutant mixture and pediatric asthma exacerbations

Abstract: Background: Exposure to air pollutants is known to exacerbate asthma, with prior studies focused on associations between single pollutant exposure and asthma exacerbations. As air pollutants often exist as a complex mixture, there is a gap in understanding the association between complex air pollutant mixtures and asthma exacerbations. We evaluated the association between the air pollutant mixture (52 pollutants) and pediatric asthma exacerbations. Method: This study focused on children (age ≤ 19 years) who li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…In Shanghai, according to Liu et al, short-term exposure to ambient air pollutants raises the frequency of pediatric visits to the Asthma Emergency Department (ED) ( 39 ). According to the findings of Puvvula et al, exposure to air pollution mixtures (primarily PM2.5, pollen, and mold) can increase emergency room (ED) visits for children with asthma ( 40 ). To sum up, air pollution (particularly PM2.5) leads to an increase in the need for asthma-related healthcare, and PM2.5 has an impact on the development and aggravation of childhood asthma.…”
Section: Resultsmentioning
confidence: 99%
“…In Shanghai, according to Liu et al, short-term exposure to ambient air pollutants raises the frequency of pediatric visits to the Asthma Emergency Department (ED) ( 39 ). According to the findings of Puvvula et al, exposure to air pollution mixtures (primarily PM2.5, pollen, and mold) can increase emergency room (ED) visits for children with asthma ( 40 ). To sum up, air pollution (particularly PM2.5) leads to an increase in the need for asthma-related healthcare, and PM2.5 has an impact on the development and aggravation of childhood asthma.…”
Section: Resultsmentioning
confidence: 99%
“…The study also conducted age-based subgroup analyses of children (0–14) and adults (>14) and found children with asthma were more susceptible to outdoor air pollution ( Huang et al 2021 ). However, various other time-series studies using air pollutants have observed a lag effect with varying results from 0–5 days ( Ostro et al 2001 , Lee et al 2006 , Halonen et al 2008 , Khalili et al 2018 , Lu et al 2020 , Puvvula et al 2022 ) to 6–7 days ( Chien et al 2018 , Dabrowiecki et al 2022). In general, lag effects past 7 days are typically not observed, though Gu et al (2004) found a lag of 7–10 days.…”
Section: Discussionmentioning
confidence: 96%
“…The same study also conducted age-based subgroup analyses of children (0–14) and adults (> 14) and found children with asthma were more susceptible to outdoor air pollution [ 36 ]. However, various other time-series studies using air pollutants have observed a lag effect with varying results from 0–5 days [ 33 , 39 , 51 , 58 , 68 , 72 ] to 6–7 days [ 15 ]. Our study, using the DLM, places the PM 2.5 associated increased risk in children’s asthma events on the higher delayed end of these studies at a weekly average lag of 7–13 days.…”
Section: Discussionmentioning
confidence: 99%